Dual apprenticeships in Mexico: Insights into the first employment - Jimena Hernández-Fernández; Erik Marsan (International Journal for Research in Vocational Education and Training (IJRVET), 2026)
Context: Dual apprenticeships (DA) are a type of Technical and Vocational Education and Training (TVET) that emphasize the development of work skills through collaboration between the education sector and the labour market. DA are believed to facilitate smoother transitions to work for youth by combining vocational training in schools with workplace-based learning. Despite claims of improving youth employability, evidence on DA's effectiveness is limited, especially outside Europe. This study investigates the employability outcomes of graduates from the Mexican adaptation of the DA model.~ Approach: The study utilizes a survey conducted with DA graduates in Mexico in 2021 to analyse their likelihood of securing employment post-graduation. A probit model is used to estimate the probability of employment across three scenarios: (1) Securing any type of job, (2) being employed by the company where the DA was completed, and (3) obtaining employment with social security, which serves as a proxy for formal employment. The dependent variables are not mutually exclusive, as overlaps exist between the different employment categories. The sample includes 307 graduates from Coahuila and the State of Mexico, and the analysis controls for individual characteristics and contextual factors.~ Findings: The analysis reveals that receiving job-relevant additional training (e.g., language courses) significantly increases the probability of securing both general employment and formal employment with social security. Similarly, longer participation in DA improves employment chances across all models, though with smaller effects. Gender disparities are evident, as women are less likely to obtain formal employment compared to men. Additionally, graduates from the Electricity and Electronics field have higher employment probabilities than their peers in service-related training areas; while graduates from the Technology and Transportation careers have lower chances of obtaining formal employment than their peers in service-related training areas.~ Conclusion:~While DA in Mexico shows promising results in employability for graduates, significant areas require attention to ensure equitable and widespread benefits. Policies should focus on increasing access to job-relevant training and extending the duration of apprenticeships to enhance apprentices' opportunities for formal employment. Our findings underscore the importance of local conditions and economic structures in shaping employment opportunities and, ultimately, DA outcomes.
Keywords: 330; Apprenticeship; Education and Training System; Employment Opportunity; Transition From Education and Training to Employment; Vocational Education and Training; VET